Robotically-assisted neuro-endovascular procedures: Single-Center Experience and a Review of the Literature. Issue 2 (April 2023) - Costa, Matias; Tataryn, Zachary; Alobaid, Abdullah; Pierre, Clifford; Basamh, Mohammed; Somji, Mohamed; Loh, Yince; Patel, Akshal; Monteith, Stephen
Introduction: Robotics could expand treatment of rapidly progressive pathologies such as acute ischemic stroke, with the potential to provide populations in need prompt access to neuro-endovascular procedures. Methods: Robotically-assisted (RA) neuro-endovascular procedures (RANPs) performed at our institution were retrospectively examined (RA-group, RG). A control group of manual neuro-endovascular procedures was selected (manual group, MG). Total operating room (OR) time, procedural time, contrast media use, fluoroscopy time, conversion from RA to manual control, procedural success, and complication rates were compared. A learning curve was identified. Results: Forty-one (41) RANPs were analyzed. Ages ranged from 20–82 y.o. Indications included diagnostic cerebral angiography (37), extracranial carotid artery stenting (3), and transverse sinus stent (1). Total OR time was longer in RG (median 86 vs. 71 min, p < 0.01). Procedural time (median 56 vs. 45 min, p = 0.12), fluoroscopy time (median 12 vs. 12 min, p = 0.69) and contrast media usage (82 vs. 92 ml, p = 0.54) were not significantly different. Patient radiation exposure was similar, considering similar fluoroscopy times. Radiation exposure and lead apron use were virtually absent for the main surgeon in RG. Procedural success was 83% and conversion from RA to manual control was 17% in RG. No treatment-related complications occurred. A learning curve showed that, after the fifth procedure, procedural times reduced and stabilized. Conclusions: This series may contribute to further demonstrating the safety and feasibility of RANPs. RANPs can potentially reduce radiation exposure and physical burden for health personnel, expand acute cerebrovascular treatment to underserved areas, and enhance telementoring. Prospective studies are necessary for results to be generalized.